Opportunities, obstacles and challenges of nano-immunotherapy in melanoma - Shan, Zexing; Liu, Fei (Frontiers in Immunology, 2025)
Melanoma is an exceptionally aggressive form of skin cancer, and its prognosis becomes dire once it metastasizes. Although substantial progress has been made in the field of immunotherapy, significant hurdles such as tumor cell immune evasion, the tumor microenvironment (TME), and immune-related adverse effects persist. Recent advancements in nanotechnology offer promising solutions to these challenges by enhancing targeting, stability, and delivery of immunotherapeutic agents. Nano-immunotherapy, which synergizes nanotechnology with immunotherapy, is evolving into a groundbreaking approach for melanoma treatment. Various nanoparticles, including liposomes, dendrimers, and polymeric nanoparticles (PNPs), are under investigation to boost immune responses, deliver immune checkpoint inhibitors (ICIs), and modulate the TME. These nanoparticles can be engineered for precise drug delivery, minimizing off-target effects and enhancing therapeutic outcomes. Moreover, the encapsulation of sensitive molecules such as cytokines, vaccines, and antibodies within nanoparticles ensures their stability and bioavailability. This review delves into the recent advancements in nano-immunotherapy for melanoma, emphasizing the mechanisms through which nanoparticles enhance immune activation and counteract the immunosuppressive TME. Additionally, we address the challenges of translating these nanomaterials into clinical settings, including optimizing nanoparticle design, ensuring safety, and achieving robust immune activation. This review provides a detailed examination of the current landscape and future potential of nano-immunotherapy as a promising strategy for melanoma treatment.